Wired / Wireless Internet Communication 10th International Conference, WWIC 2012, Santorini, Greece, June 6-8, 2012, Proceedings - Koucheryavy, Yevgeni; Mamatas, Lefteris; Matta, Ibrahim; Tsaoussidis, Vassilis (Computer Communication Networks and Telecommunications, 2012)
This book constitutes the refereed proceedings of the 10th International Conference on Wired / Wireless Internet Communications, WWIC, held in Santorini island, Greece during June 6-8, 2012. The 23 revised full papers and 6 short papers presented were carefully reviewed and selected from 50 submissions. The papers are organized in six thematically-distinct technical sessions, covering the following major topics: virtual networks and clouds, multimedia systems, wireless sensor networks and localization, delay-tolerant and opportunistic networks, handover techniques and channel access, and ad hoc networks.